Appraising the Evidence Supporting Choosing Wisely® Recommendations. Issue 10 (25th April 2018) - Admon, Andrew J.; Gupta, Ashwin; Williams, Margaret; Valley, Thomas S.; Sjoding, Michael W.; Wiener, Renda Soylemez; Cooke, Colin R.
Abstract : Despite the growing enthusiasm surrounding the Choosing Wisely ® campaign, little is known regarding the evidence underlying these recommendations. We extracted references for all 320 recommendations published through August, 2014, including the 10 adult and pediatric recommendations published by the Society for Hospital Medicine. We then categorized each item by evidence strength, and then assessed a sample of referenced clinical practice guidelines (CPGs) using the validated Appraisal of Guidelines for Research and Evaluation (AGREE) II instrument. Among all recommendations, 70.3% cited CPGs, whereas 22.2% cited primary research as their highest level of evidence. Moreover, 7.8% cited case series, review articles, editorials, or lower quality data as their highest level of evidence. Hospital medicine recommendations were more likely to cite CPGs (90%) as their highest level of evidence. Among the sampled CPGs, the median overall score obtained using AGREE II was 54.2% (interquartile range [IQR] 33.3%‐70.8%), whereas among hospital medicine‐referenced CPGs, the median overall score was 58.3% (IQR 50.0%‐83.3%). These findings suggest that Choosing Wisely® recommendations vary in terms of evidence strength.